ANALISIS EFEKTIFITAS PEMBERIAN EKSTRAK BAWANG MERAH (Allium Ascalonicum L) TERHADAP PENURUNAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH (RATTUS NORVEGICUS) DENGAN HIPERGLIKEMIA - Deinike Wanita Marwan; Faisal Faisal; Shania Mili (Collaborative Medical Journal, 2024)
Background: Hyperglycemia is a medical condition in the form of an increase in blood glucose levels exceeding normal limits. Hyperglycemia is one of the hallmarks of diabetes mellitus (DM). In 2012 diabetes was the direct cause of 1.5 million deaths globally. Where hyperglycemia is ranked second as the highest risk factor for death. Hyperglycemia that is not treated immediately will persist and can cause chronic disease, namely diabetes mellitus. Shallots have high antioxidant activity, antioxidants and quercetin are beneficial for health and can be beneficial for lowering cholesterol and blood sugar levels. Shallots have the potential to inhibit sugar metabolism in the human body, therefore red onions can be used as an anti-hyperglycemic food ingredient. Objective: To determine the effect of red onion extract on reducing blood glucose levels in rats with hyperglycemia. Methods: This study is an experimental study with a pre and post-test control group research design and uses a sample of 30 rats which will be divided into 5 groups randomly with each group consisting of 5 rats including treatment groups I, II, III given onion extract at a dose of 400 mg/kgBB, 600 mg/kgBB and 800 mg/kgBB. The positive control group was given acarbose and the negative control group was given. Observations were carried out for 14 days, data analysis was carried out with the One Way Anova test and continued with the Bonferroni Post Hoct Test. Results: The decrease in blood glucose levels was seen significantly in the treatment group III with a dose of shallot extract 800Kg/BW, with a mean decrease of 103.17Â±9.23 mg/dl with the administration of shallot extract for 14 days. Conclusion: Shallot extract (Allium ascalonicum L) can reduce blood glucose levels in hyperglycemic rats with a significant decrease in the administration of 8 ml onion extract every day for two weeks.